HUBUNGAN PERSEPSI IBU DENGAN KEPATUHAN IBU DALAM PEMBERIAN IMUNISASI DASAR PADA BALITA (STUDI DI 7 PUSKESMAS KOTA SEMARANG) - Ferina Hana Tunjung Trisna; Lintang Dian Saraswati; Ari Udiyono; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Immunization programs are one form of health intervention that is very effective in efforts to reduce infant and under-five mortality. Immunization is the main basis of service in the field of prevention and is a priority. The city of Semarang in 2017 has reached the target of complete basic immunization but there are 7 Puskesmas that have not yet reached the target of complete basic immunization. The aim of this studied was to analyze the relationship of perceptions of mothers with maternal compliance in the provision of basic immunization in infants in 7 areas of Semarang City health centers such as perceptions of vulnerability, perception of seriousness, perception of benefits and perceptions of barriers. This research is an analytical observational study with Case Control study design. The population of case group 67 and control group 459. The size of the sample in this study was 134 respondents consisting of 67 case groups and 67 control groups selected using proportional random sampling techniques. Data collection is done by interviewing using a questionnaire. Bivariate analysis using Chi-square with 95% significance. Bivariate analysis showed that perceptions of vulnerability (p = <0.001, OR: 0.145; 95% CI 0.066-0.319), perceptions of seriousness (p = 0.464), perceived benefits (p = 0.075), perceived barriers (<0.001, OR: 0.035; 95% CI 0.013-0.090). It can be concluded that there is a relationship between perceptions of vulnerability and perceived barriers to maternal compliance in providing basic immunization to infants. It is recommended for mothers to synchronize perceptions about immunization with